Progressive supranuclear palsy and corticobasal degeneration: novel clinical concepts and advances in biomarkers - Jacy Bezerra Parmera; Marcos Castello Barbosa de Oliveira; Roberta Diehl Rodrigues; Artur Martins Coutinho (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) are sporadic adult-onset primary tauopathies clinically classified among the atypical parkinsonian syndromes. They are intrinsically related with regard to their clinical features, pathology, biochemistry, and genetic risk factors. Objectives: This review highlights the current knowledge on PSP and CBD, focusing on evolving clinical concepts, new diagnostic criteria, and advances in biomarkers. Methods: We performed a non-systematic literature review through the PubMed database. The search was restricted to articles written in English, published from 1964 to date. Results: Clinicopathologic and in vivo biomarkers studies have broadened PSP and CBD clinical phenotypes. They are now recognized as a range of motor and behavioral syndromes associated with underlying 4R-tauopathy neuropathology. The Movement Disorders Society PSP diagnostic criteria included clinical variants apart from the classical description, increasing diagnostic sensitivity. Meanwhile, imaging biomarkers have explored the complexity of symptoms and pathological processes related to corticobasal syndrome and CBD. Conclusions: In recent years, several prospective or clinicopathologic studies have assessed clinical, radiological, and fluid biomarkers that have helped us gain a better understanding of the complexity of the 4R-tauopathies, mainly PSP and CBD.